Perceptions of mental skill development on youth snow sports athletes: A qualitative interview study - Müller, P. O.; Schwarzer, U.; Collins, D.; Frey, R.; Spörri, J. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: To achieve sporting excellence, mental skills play a crucial role; not only in optimising performance but also in developing an athlete's personality and mental health. However, there is disagreement about the definition and implementation of long-term development strategies regarding mental skills.1 The aim of this study was to explore current practices, barriers and opportunities related to mental skill development in youth snow sports athletes.